Correlation Between Self-Concept and Anxiety of Communicative Competence in English Foreign Language Learner - Fakka, Buhari; Asrifan, Andi; L, Syahrir; Amran, Nurul Aulia Ramadani (La Ogi : English Language Journal, 2022)
This research entitled “Correlation Between Self-Concept and Anxiety of Communicative Competence in English as Foreign Language Learner”. Common problem in this research is to find 1) Whether any correlation between Self-Concept and Anxiety toward communicative competence or not?, 2) How high a level of positive self-concept and anxiety does the student have?. The subjects of this study were students of Muhammadiyah Sidenreng Rappang University, Consisting of 21 Students as samples from fourth semester of English department. The approach used in this reaserch is quantitative by using correlation method. Data collection techniques used are questionnaire, interview and vocabullary test.Based on questionnaire and interviews with case subjects concluded that the identification of student problems are as follows: 1) There are correlation between self-concept and anxiety toward communicative competence, 2) Researcher find that student had high anxiety and mildly positive Self-concept.